Association of the time that elapsed from last vaccination with protective effectiveness against foot-and-mouth disease in small ruminants - Elnekave, Ehud (J Vet Sci, 2015)
Routine and emergency vaccination of small ruminants against foot-and-mouth disease (FMD) is mandatory in many endemic countries, yet data on the field effectiveness of the vaccines used is scarce. We conducted an investigation of a serotype O FMD outbreak that took place in a sheep and goat pen, and estimated the effectiveness of various routine vaccination statuses. We also evaluated the protection provided by colostrum administration and emergency vaccination. Animals which were routinely vaccinated twice were not clinically affected while disease incidence was observed among animals routinely vaccinated only once (p = 0.004 according to a two-sided Fisher's exact test). In groups vaccinated only once, there was a significant association between the average time that elapsed since last vaccination and the disease incidence (n = 5; Spearman correlation coefficient: r(s) = 1.0, p < 0.01). In addition, non-vaccinated lambs fed colostrum from dams vaccinated more than 2 months before parturition had a mortality rate of 33%. Administration of emergency vaccination 2 days after the occurrence of the index case was the probable reason for the rapid blocking of the FMD spread within 6 days from its onset in the pen.